If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(2x + -9) = 0 Reorder the terms: ln(-9 + 2x) = 0 (-9 * ln + 2x * ln) = 0 (-9ln + 2lnx) = 0 Solving -9ln + 2lnx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'ln'. ln(-9 + 2x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-9 + 2x)' equal to zero and attempt to solve: Simplifying -9 + 2x = 0 Solving -9 + 2x = 0 Move all terms containing l to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 2x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 2x = 0 + 9 2x = 0 + 9 Combine like terms: 0 + 9 = 9 2x = 9 Add '-2x' to each side of the equation. 2x + -2x = 9 + -2x Combine like terms: 2x + -2x = 0 0 = 9 + -2x Simplifying 0 = 9 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 3s^2+28x-3=0 | | F(x)=x^2-15x+15 | | 43-26=40-x | | 5.2x=31 | | 17x+12=17x-12 | | 5.2x=32 | | (1)(2)y-7=(1)(5)y | | 56-21=x-20 | | 13+74=x+70 | | 7h+10=66 | | 43+15=40+c | | (3x+1)(6x-4)= | | .4w+60=w+53 | | X+16=20+17 | | -2(2t+1)=2 | | 48+x=47+31 | | .4w+60=1w+53 | | 9-8m=17 | | (x^2)-4x=6 | | 7m+1-1=4m+6m | | -3x+6x+24=9 | | 4+x=7+2 | | .4w+60=e+53 | | r+2r+3r=4 | | 4(f-8)=-16 | | 10m-21=79 | | V+15=7 | | 6z+3z=63 | | -3x+4=3 | | 8=8z | | 2000+.56x=545+73x | | -10(s+1)=63 |